2020
DOI: 10.1093/schbul/sbz128
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition and Adverse Childhood Experiences in Individuals at Clinical High Risk of Psychosis

Abstract: Abstract Objective To investigate the association between facial affect recognition (FAR) and type of adverse childhood experiences (ACEs) in a sample of clinical high risk (CHR) individuals and a matched sample of healthy controls (HCs). Methods In total, 309 CHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 71 publications
1
18
0
1
Order By: Relevance
“…The mechanisms by which stigma impairs cognitive performance include distraction and loss of focus presumably due to increased stereotyped-related distraction (Cadinu et al, 2005), increased physiological arousal such as decreased heart rate variability (Croizet et al, 2004), increased skin conductance and blood pressure (Osborne, 2006), and increased anxiety (Spencer et al, 1999). The relationship between stigma and social cognitive processing is also supported by work showing that adverse experiences impact cognitive processing of emotional stimuli in individuals with CHR (Tognin et al, 2020) and with evidence for overlap in the neural underpinnings of stigma and emotion detection (Clark et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The mechanisms by which stigma impairs cognitive performance include distraction and loss of focus presumably due to increased stereotyped-related distraction (Cadinu et al, 2005), increased physiological arousal such as decreased heart rate variability (Croizet et al, 2004), increased skin conductance and blood pressure (Osborne, 2006), and increased anxiety (Spencer et al, 1999). The relationship between stigma and social cognitive processing is also supported by work showing that adverse experiences impact cognitive processing of emotional stimuli in individuals with CHR (Tognin et al, 2020) and with evidence for overlap in the neural underpinnings of stigma and emotion detection (Clark et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. STIGMA AND EMOTION RECOGNITION IN PSYCHOSIS-RISK emotional stimuli in individuals with CHR (Tognin et al, 2020) and with evidence for overlap in the neural underpinnings of stigma and emotion detection (Clark et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…AP group subjects with atypical antipsychotics, FFX fixed effects analysis, FWE family-wise error of schizophrenia [18,19]. Early detection of specific symptoms in schizophrenia [20][21][22][23] seems to be crucial and may also have a prognostic value [24]; early intervention in schizophrenia spectrum disorders appears to be important [25][26][27][28] and it has been suggested that cognitive training should be provided as early as possible in the prodromal phases of schizophrenia in order to use the full rehabilitative potential of the subjects [29]. Indeed, Bowie et al [30] found that cognitive remediation in the early course leads to greater cognitive improvement than in later stages of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The course of cognitive deficits has been described to be different between early and late stages of schizophrenia [ 18 , 19 ]. Early detection of specific symptoms in schizophrenia [ 20 23 ] seems to be crucial and may also have a prognostic value [ 24 ]; early intervention in schizophrenia spectrum disorders appears to be important [ 25 28 ] and it has been suggested that cognitive training should be provided as early as possible in the prodromal phases of schizophrenia in order to use the full rehabilitative potential of the subjects [ 29 ]. Indeed, Bowie et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a substantial number of patients with BPD report having experienced childhood maltreatment (McFetridge et al, 2015 ; Temes et al, 2017 ; Zanarini et al, 1997 ). However, various studies indicate that childhood maltreatment is also a risk factor for other mental health disorders such as depressive disorders (DD) (Isvoranu et al, 2016 ; Nelson, Klumparendt, Doebler, & Ehring, 2017 ; Tognin et al, 2020 ; Vallati et al, 2020 ), which are among the most prevalent mental health disorders. Several studies found elevated scores of self-reported childhood maltreatment in patients with DD compared to healthy controls (Brakemeier et al, 2018 ; Carvalho Fernando et al, 2014 ; Kaczmarczyk, Wingenfeld, Kuehl, Otte, & Hinkelmann, 2018 ; Meinert et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%